2021
DOI: 10.1159/000519581
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Receiving a Diagnosis of Alzheimer’s Disease and Related Dementias on Social Relationships of Older Adults

Abstract: <b><i>Introduction:</i></b> Although early diagnosis has been recognized as a key strategy to improve outcomes of Alzheimer’s disease and related dementias (ADRD), the effect of receiving a diagnosis on patients’ well-being is not well understood. This study addresses this gap by examining if receiving a dementia diagnosis influences social relationships. <b><i>Methods:</i></b> Data from the 3 waves (2012, 2014, and 2016) of the Health and Retirement Study were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 32 publications
2
18
1
Order By: Relevance
“…Our findings also indicated that a diagnostic label of ADRD may reduce the social engagement of recipients. This is consistent with relatively rich evidence of social disengagement among people with ADRD 22,23,70–72 . This study strengthened the evidence by utilizing a larger sample and more robust statistical methods.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Our findings also indicated that a diagnostic label of ADRD may reduce the social engagement of recipients. This is consistent with relatively rich evidence of social disengagement among people with ADRD 22,23,70–72 . This study strengthened the evidence by utilizing a larger sample and more robust statistical methods.…”
Section: Discussionsupporting
confidence: 86%
“…We advance the evidence by showing, with a quasi‐experimental study design, that a diagnostic label of ADRD may contribute to increasing informal and formal social support among people with ADRD. Interestingly, this is partially inconsistent with a previous study that revealed that dementia diagnoses did not change perceived social support 22 . Although a direct comparison may not be possible, this inconsistency implies that unmet needs may still remain despite increases in support after a diagnosis 66,67 .…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…However, when dementia is not acknowledged as a factor behind social changes, more negative consequences, including social isolation, can occur (46). Along similar lines, (47) have suggested that being diagnosed with dementia may have unintended effects for social relationships, such as decreases in social activities.…”
Section: Changes In Social Relationshipsmentioning
confidence: 91%
“…They also recommend that these should be considered when developing dementia-specific interventions [2]. Many people with dementia have the ability to maintain an active and social life, but some of the negative effects of receiving a diagnosis, depression, or diagnosis stigma can result in social isolation and withdrawal from society [3,4]. It is important that people living with mild dementia are supported and encouraged to maintain their normal activities, remain independent, and stay active within society for as long as they are able to.…”
Section: Introductionmentioning
confidence: 99%